PECULIARITIES OF DEVELOPMENT OF COUNTRIES WITH ECONOMIES IN TRANSITION - Акбарова Мохинур Фарход кизи (Scholars Digest Publishing, 2024)
Countries with economies in transition represent a unique group of states that have undergone or continue to undergo the process of transition from a planned economy to a market economy. The article examines this transition, which is often accompanied by significant economic and social challenges, and countries in this position face a number of challenges in their development.
Keywords: transition economy, liberalization, restructuring, integration, investment, privatization.